IMF Support and Crisis Prevention - Ghosh, Atish (Occasional Papers; Occasional Paper, 2008)
This paper examines the various roles of IMF financing in crisis prevention. Emerging market economies that experienced financial crises in the past have been subject to enormous economic and social costs, highlighting the importance of crisis prevention. While the main defense against a crisis lies in a country's own policies and institutional framework, the IMF can contribute to these efforts through its surveillance activities, provision of technical assistance, and promotion of standards and codes. But the IMF may be able to contribute to crisis prevention more directly by providing contingent financial support. This paper explores the theoretical basis of, and empirical evidence for, possible 'crisis prevention programs.'.